(untitled) (Research, Society and Development, 2021)
The acceptability of the processed cheese is related to the texture which, among other factors, is influenced by the fat content. The aim of this study was to analyze the sensory acceptability of two commercial brands of traditional and light processed cheese (TA, TB, LA, LB) and perform the correlation with instrumental measurements of texture. The sensory evaluation was performed with 121 untrained panelists, using the acceptance tests by hedonic scale of 9 points for attributes overall impression, appearance, smell, texture and flavor and Check-All-That-Apply (CATA) with 12 descriptive terms. To evaluate the Instrumental Texture Profile (TPA), three tests were performed in triplicate on a texture analyzer. The four samples obtained acceptance with mean scores between 6.45 and 7.74 and an Acceptability Index greater than 70% for all attributes. The sensory assessors identified a significant difference between the processed cheese for each sensory term covered in the CATA. For TPA, the only parameter that showed no difference (p≥0.05) was elasticity. Correspondence Analysis explained 98.82% of the variation. The correlation of sensory and instrumental measurements indicated that the texture of brand B, regardless of the process has the same characteristics. In the A brand, the influence of the fat content in the processing was noticeable, as the evaluators distinguished the processed cheese LA from the TA, showing that the manufacturing process allowed the differentiation in terms of texture and sensory attributes.